Development and Validation of Contextualized Kindergarten Module for Children with Hearing Impairment - Guzman, Sammy Boy B. (Future Science / FSH-PH Publications, 2024)
This study aimed to develop and validate a sign language-based and contextualized kindergarten module for children with hearing impairment. There is a need to develop and contextualize a module in order to cater the unmet needs of students with hearing impairment. The developed module includes a teaching guide for parents, for them to become more effective co-facilitators of learning. The distinctive feature of this module is that, the sign language interpretations are with pictures and texts. The pictures vividly show the step-by-step procedure on how to sign the specific word. The pictures are supported by the comprehensive explanation on how to sign the words. This study utilized the Research and Development (R & D) research method to systematically design, develop and evaluate the instructional material. The participants of this study are eleven (11) students with hearing impairment and eleven (11) parents of students with hearing impairment. The respondents and served as expert-validators are master teacher, kindergarten teacher, and SPED teacher. It employed a purposive sampling technique; it purposely selected a population related to children with hearing impairment. To analyze the qualitative data, it was imported to MAXQDA software with the use of Horizontalization method by Moustakas. For statistical treatment of the descriptive data, researchers used the PSPP software. The study found that the parents’ ideal module for children with hearing impairment has five emerging themes, such as 1) sign language medium of instruction, 2) disability consideration, 3) media consideration, 4) level of difficulty, and 5) technical design. Expert-validators assessed that the validity of contextualized kindergarten module is highly acceptable among the dimensions of: content, format and language, presentation, and usefulness. Effectiveness of the contextualized module as perceived by the parents yielded a total of 96.36% positive responses.